2019
DOI: 10.1111/1751-7915.13454
|View full text |Cite
|
Sign up to set email alerts
|

A panel of recombinant proteins for the serodiagnosis of caseous lymphadenitis in goats and sheep

Abstract: Summary Caseous lymphadenitis (CLA) is a small ruminant disease characterized by the development of granulomatous lesions in superficial and internal lymph nodes, as well as in some organs, and causes significant economic losses worldwide. The aetiological agent of CLA is the bacterium Corynebacterium pseudotuberculosis; however, the commercially available diagnostic tools present problems with regard to specificity, which can lead to false‐negative results. This study aimed to develop an indirect enzyme‐linke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 35 publications
(55 reference statements)
1
22
0
2
Order By: Relevance
“…In the present study, the standardized test using rSodC protein showed satisfactory performance in the identi cation of positive and negative cases of C. pseudotuberculosis by serological responses, both in the initial standardization tests and in validation tests with goat and sheep samples. The use of this protein as an antigen to diagnose CL is promising due to the observed high sensitivity and speci city values, which were comparable or superior to those described in the literature to detect goats and sheep infected with C. pseudotuberculosis using different recombinant antigenic preparations (Menzies et al 2004;Rezende et al 2016;Barral et al 2019).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…In the present study, the standardized test using rSodC protein showed satisfactory performance in the identi cation of positive and negative cases of C. pseudotuberculosis by serological responses, both in the initial standardization tests and in validation tests with goat and sheep samples. The use of this protein as an antigen to diagnose CL is promising due to the observed high sensitivity and speci city values, which were comparable or superior to those described in the literature to detect goats and sheep infected with C. pseudotuberculosis using different recombinant antigenic preparations (Menzies et al 2004;Rezende et al 2016;Barral et al 2019).…”
Section: Discussionmentioning
confidence: 59%
“…Currently, there are no reliable tests available to diagnose all CL cases. ELISA, using several antigenic preparations, has already been tested (Sutherland et al 1987;Menzies et al 1994;Sting et al 1998;Carminati et al 2003); however, few formulations use recombinant proteins (Menzies et al 1994;Rezende et al 2016; Barral et al 2019;Silva et al 2019). This strategy could signi cantly increase sensitivity and speci city due to the use of a single puri ed antigen (Rezende et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…As they are puri ed antigens, recombinant proteins can improve speci city, reducing the chances of cross reactions with molecules of other microorganisms. They can also in uence sensitivity, since the amount of immunodominant protein used to sensitize the plaques is greater than the concentration of this molecule in a raw antigen extract (Barral et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In the rst validation step, recombinant SodC protein was selected to be tested with positive serum control samples from 50 goats and 45 sheep in which C. pseudotuberculosis infection was con rmed by isolating bacteria from caseous lesions. Samples from 50 goats and 45 sheep from CL nonendemic areas in southern Brazil, where there are strict controls for introducing new animals, were used as a negative control (Barral et al 2019).…”
Section: Validationmentioning
confidence: 99%
See 1 more Smart Citation